The Impact of Village Fund Utilization on Embung Agricultural Infrastructure Development on Community Socio-Economic Activities - Nur Zaman (Lowland Technology International, 2020)
One of the agents and development of the Indonesiangovernment nationally is to develop Indonesia from the marginsthat are considered left behind by strengthening regions andvillages within the framework of a unitary state throughthe policy of Law Number 6 of 2014 concerningVillages. Utilization natural resources is one of the mainaspects to achieve the objectives of rural development, namelyimproving the welfare of rural communities and the quality ofhuman life and reduce poverty . This study aimed todescribe the effect of utilization village fund on Embunginfrastructure development to the public economy. The methodused in this research is a qualitativedescriptive analysis method. Aspects of the easel d i priorities inthis study consisted of that aspect of the planning,environmental, infrastructure aspects, institutional aspects,social aspects and the economic aspects. The result show thatthe existence of infrastructure E mbung very helpful, because onrainy season, as a place to hold water , on the drought , asthe need for irrigation to irrigate the fields, the fields d early fortheir daily needs